Numerical and experimental investigations of hydrodynamics of a fully-enclosed pile-net aquaculture pen in regular waves - Cui, Yong; Wang, Gang; Guan, Chang-tao (Frontiers in Marine Science, 2023)
Large-scale aquaculture pen is one of the essential modes of offshore aquaculture being explored in recent years. In contrast to cage farming, the advantages are more significant as the larger cultural space for fish swimming, the closer-to-nature environment, and the improved ecological quality of fish. As a novel offshore aquaculture structure, fully-enclosed pile-net aquaculture pens (FPAPs) are generally deployed in exposed oceans, where severe waves and currents are of great dominance. The hydrodynamic characteristics of FPAPs in offshore areas deserve further investigation. In this paper, the numerical model of a typical FPAP in waves is proposed based on the finite element method (FEM), then wave loads on and induced motion responses of the FPAP are analyzed. The results show that the maximum loads on the structure and the maximum displacement of piles are closely proportional to the wave height. Secondly, the maximum stress of nets decreases as the embedded depth increases, while the deformation of nets tends to rise with the increase of pile spacing. At last, several structural optimal patterns are given to improve the safety of pen facilities. This work has laid a solid scientific foundation for designs and optimizations of FPAPs in the future.